Layouts and spatial configurations: on the trail of urban heritage in Quibdó, Colombia (2021)
The article makes a reflection on the conformation of the urban layout of the city of Quibdó, in the Colombian Pacific, in relation to the spatial configurations that constitute it and that this constitutes. This proposal understands the conformation of the layout and the spaces in correlation with diverse social relations, in the knowledges, understandings, appropriations and experiences of the local groups, as well as in the relations of the settlers with the physical and natural environment, as weavings of relations and dynamics that build space and territory. From the research carried out in the urban structure of Quibdó, spatial configurations and characteristic layouts of the city are identified, through which are traced understandings, identities and forms of thought and organization associated with space. The inquiries lead to the detection of elements of value associated both with spatialities and layouts that allow glimpses of heritage elements linked to the urbanscape. It is a bet to understand other forms of approach that put in tension the hegemonic look that catalogs and dictates what is the urban heritage of this city.